Implementasi Website Desa sebagai Media Informasi dan Transparansi Pemerintahan di Desa Jogoloyo Kab. Jombang - Muhamad Khoirur Roziqin; Yesi Wulan Puspitasari; Lusi Yuni Astuti; Nur Holis; Mukhammad Nasrul Wahada; Faizah Muzaqiyafin (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2026)
Village government faces signiticant challenges in information dissemination and transparency implentation du to limited digital infrastructure and human resources capacity. This community service aimed to develop a village website as an information medium and transparency tool for Jogoloyo Village government. The participatory development method was employed, involving needs assessment, codesign, capacity building, and community engagement. The developed website (https://desajogoloyo.com) features 18 main paes including administrative services, budget transparency modules, MSME (Micro, Small Medium Enterprise) directories, and public complaint systems. Result showed improved information accessbility, enhanced operational efficiency trough digitization of administrative processes, increased public satisfaction from 3.2 to 4.2 (scale 5), and enhanced government trasparency. The website successfully facilitates two-way communication between village government and community, supporting good governance principles. This initiative demonstrates the potential of digital technology in transforming rural governance and can serve as a replication model for other villages.